Clinically oriented anatomy - Moore, Keith L. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2014)
"Clinically Oriented Anatomy provides first-year medical students with the clinically oriented anatomical information as it relates to the practice of medicine, dentistry, and physical therapy. The 7th edition features a fully revised art program to ensure consistency and cohesiveness of imaging style"--Provided by publisher.